Aged Mice are Unable to Mount an Effective Myeloid Response to Sepsis - Nacionales, Dina C. (2013)
The elderly have increased morbidity and mortality following sepsis; however, the cause(s) remain unclear. We hypothesized that these poor outcomes are due in part to defects in innate immunity, rather than to an exaggerated early inflammatory response. Juvenile (6–12 weeks) or aged (20–24 months) mice underwent polymicrobial sepsis and subsequently, the aged mice had increased mortality and defective peritoneal bacterial clearance compared to young mice. No differences were found in the magnitude of the plasma cytokine responses. Although septic aged mice displayed equivalent or increased numbers of circulating, splenic and bone marrow myeloid cells, some of these cells exhibited decreased phagocytosis, reactive oxygen species production and chemotaxis. Blood leukocyte gene expression was less altered in aged versus young mice one day after sepsis. Aged mice had a relative inability to upregulate gene expression of pathways related to ‘PMN-mediated protective immunity’, ‘chemokine/chemokine receptor binding’ and ‘responses to exogenous molecules’. Expression of most MHC genes remained more down-regulated in aged mice at day three. Despite their increased myeloid response to sepsis, the increased susceptibility of aged mice to sepsis appears not to be due to an exaggerated inflammatory response, but rather, a failure to mount an effective innate immune response.